Handbook on the globalisation of agriculture - Guy M. Robinson & Doris A. Carson (Editor) (Cheltenham, UK Edward Elgar Publishing, 2015)
Agriculture is becoming increasingly influenced by globalisation. The result is a more interconnected world where new forms of trade and cultural exchange can thrive on an international level. This novel Handbook provides insights to the ways in which globalisation is affecting the whole agri-food system, from farms to the consumer. The expert contributors cover themes including the physical basis of agriculture, the influence of trade policies, the nature of globalised agriculture, and resistance to globalisation in the form of attempts to foster sustainability and multifunctional agricultural systems. They present a state-of-the-art summary of current debates and provide a starting point for subsequent research into solutions aimed at addressing food insecurity, global hunger and uneven development. Drawing upon studies from around the world, the Handbook will appeal to a broad and varied readership, across academics, students, and policy-makers interested in economics, trade, geography, sociology and political science. -- Source otjher than Library of Congress.
Includes bibliographical references and index
Keywords: Agriculture--Economic aspects